2021
DOI: 10.3390/jcm10163504
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Statin Treatment According to Baseline Renal Function in Korean Patients with Acute Myocardial Infarction Not Requiring Dialysis Undergoing Newer-Generation Drug-Eluting Stent Implantation

Abstract: We investigated the 2-year efficacy of statin treatment according to baseline renal function in patients with acute myocardial infarction (AMI) not requiring dialysis undergoing newer-generation drug-eluting stent (DES) implantation. A total of 18,875 AMI patients were classified into group A (statin users, n = 16,055) and group B (statin nonusers, n = 2820). According to the baseline estimated glomerular filtration rate (eGFR; ≥90, 60–89, 30–59 and <30 mL/min/1.73 m2), these two groups were sub-classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Three studies on pharmacotherapy were also conducted in Korea and Japan. Kim et al [ 8 ] reported that the prognostic benefit of statin therapy following PCI for acute myocardial infarction (AMI) was significant even in patients with advanced renal impairment, compared to non-statin users. However, since the incidence rate of adverse events in patients with chronic kidney disease is still high, further therapeutic approaches are needed, especially in these patient populations.…”
mentioning
confidence: 99%
“…Three studies on pharmacotherapy were also conducted in Korea and Japan. Kim et al [ 8 ] reported that the prognostic benefit of statin therapy following PCI for acute myocardial infarction (AMI) was significant even in patients with advanced renal impairment, compared to non-statin users. However, since the incidence rate of adverse events in patients with chronic kidney disease is still high, further therapeutic approaches are needed, especially in these patient populations.…”
mentioning
confidence: 99%